Laparoscopic Extraperitoneal Para-Aortic Lymphadenectomy in the Staging of Locally Advanced Cervical Cancer: Is it a Feasible Procedure at a Peripheral Center?. Issue 2 (1st February 2012) - Benito, Virginia; Lubrano, Amina; Arencibia, Octavio; Andújar, Miguel; Pinar, Beatriz; Medina, Norberto; Falcón, Juan Miguel; Falcón, Orlando
Abstract : Objective: The study's aim was to evaluate the feasibility of laparoscopic extraperitoneal para-aortic lymphadenectomy at a peripheral center for the staging of patients with locally advanced cervical cancer (LACC). Methods: From March 2009 to January 2011, 30 patients with LACC underwent laparoscopic extraperitoneal para-aortic lymphadenectomy. All patients were treated with definitive radiotherapy tailored according to the staging results. Data on demographics, pathologic findings, surgery, complications, and disease status at follow-up are presented. Results: Patients' mean age was 47.6 years (range, 28–67 years). The mean body mass index was 26.3 (range, 19.1–35.6). Mean operative time was 118.7 minutes (range, 77–195 minutes) with an average of 14.2 lymph nodes removed (range, 5–34). Intraoperative complications were a lumbar artery injury and a bowel injury. No postoperative complications occurred. Mean postoperative hospital stay was 1.9 days (range, 1–6 days). Pathological examination revealed that 26.7% (8/30) of patients had metastatic disease in para-aortic lymph nodes. Two patients with disease at the para-aortic level died 5 and 12 months after diagnosis; both of them developed pulmonary and hepatic metastases. The rest of the patients were free of disease, after completion of the treatment, during a mean follow-up time of 15.6 months (range, 5–27 months). Conclusions: Laparoscopic extraperitoneal aortic lymphadenectomy is a feasible procedure, even at peripheral centers, that is useful to identify patients with LACC and para-aortic disease and to tailor their treatment. Gynecologic oncologists are encouraged to learn this procedure and offer it to their patients.